2021
DOI: 10.1186/s40168-021-01195-7
|View full text |Cite|
|
Sign up to set email alerts
|

Human microbiota research in Africa: a systematic review reveals gaps and priorities for future research

Abstract: Background The role of the human microbiome in health and disease is an emerging and important area of research; however, there is a concern that African populations are under-represented in human microbiome studies. We, therefore, conducted a systematic survey of African human microbiome studies to provide an overview and identify research gaps. Our secondary objectives were: (i) to determine the number of peer-reviewed publications; (ii) to identify the extent to which the researches focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 255 publications
(223 reference statements)
2
27
0
Order By: Relevance
“…In summary, in this study, we have characterized the infant gastrointestinal microbiota in children from birth to 2 years of age living in Malawi, and the information generated adds to the limited studies of the gastrointestinal microbiomes of African populations ( 80 ). We also demonstrated that Shigella infection did not profoundly impact overall species diversity but led to the expansion of species known to improve gastrointestinal health and drive the microbiota back to homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, in this study, we have characterized the infant gastrointestinal microbiota in children from birth to 2 years of age living in Malawi, and the information generated adds to the limited studies of the gastrointestinal microbiomes of African populations ( 80 ). We also demonstrated that Shigella infection did not profoundly impact overall species diversity but led to the expansion of species known to improve gastrointestinal health and drive the microbiota back to homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 5% of studies confirmed the recruitment of urban populations while 31% of all studies focused on recruitment in rural settings. Notably less than 4% of studies included more than 500 participants with only ∼1% of studies including more than 1,000 participants ( Allali et al, 2021 ). These findings highlight a clear need for coordinated intra-continental, African researcher-driven microbiome initiatives that focus on addressing the future health needs of the continent.…”
Section: Microbiome Research Efforts Globally and Across Africamentioning
confidence: 99%
“…A number of African-directed initiatives have recently been launched to investigate the role of the microbiome in human health and disease on the African continent. These studies are however traditionally limited in terms of either their scale or scope when compared to large scale microbiome profiling efforts like the AGP ( Allali et al, 2021 ). The South African Microbiome Initiative in Neuroscience, based at Stellenbosch University in SA, is a pioneering African microbiome profiling initiative ( saNeuroGut, 2017 ).…”
Section: Microbiome Research Efforts Globally and Across Africamentioning
confidence: 99%
“…The gut microbiota has attracted much research over the past years and is believed to be involved in the pathogenesis and progression of numerous diseases [ 1 , 2 ]. The gut microbiota is a complex, dynamic, and spatially diverse ecosystem that consists of countless microorganisms (bacteria, fungi, archaea, and viruses) that interact with each other, and with the human host in the gastrointestinal ecosystem [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive research that is available regarding the characterization of gut microbiota in both health and disease in Western populations [ 1 ]. These studies have generally found that the composition of gut microbiota differs significantly between healthy individuals and those who are diseased [ 23 ].…”
Section: Introductionmentioning
confidence: 99%